Local functional food: Stunting prevention in toddlers - Yarmaliza; Farisni, Teungku Nih; Fitriani; Reynaldi, Fitrah; Zakiyuddin; Fadillah, Mardi; Arundhana, Andi Imam; Syahputri, Veni Nella (jurnal1, 2024)
Functional food has emerged as a potential intervention to prevent stunting in toddlers, utilizing locally available ingredients such as tempeh and clams. These foods possess several favorable attributes, including ease of accessibility, affordability, have high nutritional value and excellent digestibility in the human body. This study introduces a novel approach by formulating tempeh broth as a substitute for clam flour, aiming to improve nutritional status and prevent stunting. The primary objective was to develop tempeh broth with substituted clam flour and evaluate the impact on organoleptic properties and nutritional value. The study involved a laboratory experiment where tempeh broth was substituted with varying amounts of claims flour: 15g (P1), 30g (P2), and 45g (P3). Organoleptic evaluation was conducted by 37 panelists using a hedonic scale technique. The analysis of the organoleptic test data comprised the normality, Friedman, and Wilcoxon Test. The findings revealed that the tempeh broth formula with a 15g clam flour substitution (P2) was the most preferred in terms of color, aroma, and taste. The substitution of clam flour in tempeh also led to an increase in the nutritional value, specifically higher protein, PUFA, vitamin A, vitamin E, vitamin B6, total folic acid, potassium, magnesium, phosphorus, ferrous and zinc. In conclusion, increasing the amount of clam flour substitution in tempeh broth resulted in higher nutritional value and had a significant effect on the organoleptic properties. The findings support the continued exploration of local functional food interventions to address nutritional deficiencies and improve public health nutrition.